Design and Validation of a Novel Smartphone-Based Visual Acuity Test: The K-VA Test - Vasileios Karampatakis; Diamantis Almaliotis; Persefoni Talimtzi; Stavroula Almpanidou (Ophthalmology and Therapy, 2023)
Abstract Introduction Visual acuity (VA) testing is a critical screening examination for the assessment of visual function. This study describes the development and validation of a smartphone-based VA test: the K-VA test. Methods A total of 171 patients with various ocular diseases were examined in our outpatient unit at Aristotle University of Thessaloniki, School of Medicine in Greece. Participants underwent VA examination using the standard Early Treatment Diabetic Retinopathy Study (ETDRS) charts and the K-VA smartphone-based test. The K-VA test was performed by participants themselves. The Bland–Altman method was employed to assess the agreement between the ETDRS charts and the new test for the examination of VA at 1 m and 40 cm. Test–retest reliability was also calculated. A questionnaire regarding the participants’ feedback on the K-VA test was completed. Results No significant bias was observed between the gold standard ETDRS charts and the K-VA test measurements. The mean difference (95% limits of agreement, LoA) between the K-VA test at 1 m and the ETDRS chart at 4 m was −0.006 (95% LoA −0.129 to 0.117) logarithm of the minimal angle of resolution (logMAR). The agreement of the K-VA test at 40 cm with the near ETDRS chart was also high with a mean difference of −0.007 (95% LoA −0.105 to 0.090) logMAR. Test–retest reliability was found to be high with a mean difference of 0.003 (95% LoA −0.045 to 0.033) logMAR and 0.005 (95% LoA −0.065 to 0.076) logMAR for the K-VA test at 1 m and 40 cm, respectively. A total of 97 participants answered the questionnaire and 71 (73.2%) stated that the test was easy to very easy to use for self-performance. Conclusions The study demonstrated that the K-VA application performed well compared with the ETDRS charts and provides reliable and repeatable measurements of VA across a wide range of VA.